Application of Purified Botulinum Type A Neurotoxin to Treat Experimental Trigeminal Neuropathy in Rats and Patients with Urinary Incontinence and Prostatic Hyperplasia. (14th June 2012) - Matsuka, Yoshizo; Yokoyama, Teruhiko; Yamamoto, Yumiko; Suzuki, Tomonori; Dwi Fatmawati, Ni Nengah; Nishikawa, Atsushi; Ohyama, Tohru; Watanabe, Toshihiro; Kuboki, Takuo; Nagai, Atsushi; Oguma, Keiji
Abstract : Type A neurotoxin (NTX) of Clostridium botulinum was purified by a simple procedure using a lactose gel column. The toxicity of this purified toxin preparation was retained for at least 1 year at −30°C by supplementation with either 0.1% albumin or 0.05% albumin plus 1% trehalose. When purified NTX was used to treat 49 patients with urinary incontinence caused by either refractory idiopathic or neurogenic detrusor overactivity, 36 patients showed significant improvement in symptoms. These beneficial effects were also observed in cases of prostatic hyperplasia. The results obtained with NTX were similar to that of Botox. The effects of NTX on trigeminal neuralgia induced by infraorbital nerve constriction (IoNC) in rats were also studied. Trigeminal ganglion neurons from ipsilateral to IoNC exhibited significantly faster onset of FM4-64 release than sham-operated contralateral neurons. Intradermal injection of NTX in the area of IoNC alleviated IoNC-induced pain behavior and reduced the exaggerated FM4-64 release in trigeminal ganglion neurons.